A Danish version of self‐efficacy in diabetes self‐management: A valid and reliable questionnaire affected by age and sex. Issue 3 (2nd November 2017) - Lindkvist, Emilie Bundgaard; Kristensen, Lene Juel; Sildorf, Stine Møller; Kreiner, Svend; Svensson, Jannet; Mose, Anne Hvarregaard; Birkebæk, Niels; Thastum, Mikael
Abstract : Background: Managing the chronic illness type 1 diabetes (T1D) is extremely demanding, especially during adolescence. Self‐efficacy is belief in one's own capabilities and this is crucial for diabetes management. Having a valid method for measuring self‐efficacy is important. Objective: Our aims were to psychometrically validate a Danish version of the self‐efficacy in diabetes management (SEDM) questionnaire, and to examine the relationship between background variables and self‐efficacy. Methods: All Danish adolescents with T1D ( n  = 1075) were invited to participate in our study. In total, 689 agreed to participate and 602 completed the study. Data were collected using a web‐based survey. All participants were asked to provide a blood sample for HbA1c measurement. Graphical log‐linear Rasch modeling (GLLRM) was used to validate the questionnaire and its reliability was assessed using Monte Carlo simulation. Results: We found the questionnaire to be valid and reliable, but it had a dual structure that suggested a need for 2 separate subscales. One subscale related to practical (SEDM1) and the other to emotional (SEDM2) aspects of diabetes management. Both subscales were targeted toward adolescents with lower self‐efficacy and were associated with HbA1c. SEDM1 was influenced by treatment modality and age. In SEDM2 we found an interaction between age and sex. Conclusion: The Danish version of the SEDM questionnaire should be divided into two parts, each with a valid and reliable subscale for self‐efficacy measurement. The relationship between self‐efficacy and age seems to differ between boys and girls.